Shear Velocity Structure From Ambient Noise and Teleseismic Surface Wave Tomography in the Cascades Around Mount St. Helens. Issue 8 (5th August 2019) - Crosbie, Kayla J.; Abers, Geoffrey A.; Mann, Michael Everett; Janiszewski, Helen A.; Creager, Kenneth C.; Ulberg, Carl W.; Moran, Seth C.
Abstract: Mount St. Helens (MSH) lies in the forearc of the Cascades where conditions should be too cold for volcanism. To better understand thermal conditions and magma pathways beneath MSH, data from a dense broadband array are used to produce high‐resolution tomographic images of the crust and upper mantle. Rayleigh‐wave phase‐velocity maps and three‐dimensional images of shear velocity ( Vs ), generated from ambient noise and earthquake surface waves, show that west of MSH the middle‐lower crust is anomalously fast (3.95 ± 0.1 km/s), overlying an anomalously slow uppermost mantle (4.0–4.2 km/s). This combination renders the forearc Moho weak to invisible, with crustal velocity variations being a primary cause; fast crust is necessary to explain the absent Moho. Comparison with predicted rock velocities indicates that the fast crust likely consists of gabbros and basalts of the Siletzia terrane, an accreted oceanic plateau. East of MSH where magmatism is abundant, middle‐lower crust Vs is low (3.45–3.6 km/s), consistent with hot and potentially partly molten crust of more intermediate to felsic composition. This crust overlies mantle with more typical wave speeds, producing a strong Moho. The sharp boundary in crust and mantle Vs within a few kilometers of the MSH edifice correlates with a sharp boundary from low heat flow in the forearc to high arc heat flow and demonstrates that the crustal terrane boundary here couples with thermal structure to focus lateral melt transport from the lower crust westward to arc volcanoes. Key Points: High wave speeds in the forearc crust of Cascadia help explain the absent Moho that is commonly ascribed to mantle hydration Lower‐crustal magma storage appears offset from the Mount St. Helens edifice, which is offset west of the main arc line Crustal structure plays a critical role in the location of volcanism and helps explain the unusual trenchward location of Mount St. Helens